An Unusual Case of Francisella tularensis - Samantha Huang; Bradley Kaptur; Julius Manu; Elias Woldegabriel (Case Reports in Infectious Diseases)
A 67-year-old male presented with complaints of weakness, fatigue, and shortness of breath in the context of a recent hospitalization for the same unresolved symptoms. After a largely nonspecific clinical presentation, a chest X-ray revealed a loculated pleural effusion. Culture of the postthoracentesis exudate revealed the culprit to be the aerobic Gram-negative bacterium Francisella tularensis. Amidst reports of potential resurgence, clinicians should be aware of the possible presentations of tularemia and consider it in the case of an ostensibly contributory patient history.